Pattern of fast or junk food consumption among medical students of north Karnataka- a cross sectional study - Nayak, Rakesh K. (International Journal Of Community Medicine And Public Health, 2020)
Background: The culture of fast food consumption is replacing the traditional meal. It is an emerging trend among the younger generation. Their ready availability, taste, low cost, marketing strategies and peer pressure make them popular. Stress in medical students’ life and study load would be factors that negatively influence their diet. Methods: A cross sectional study was carried out among undergraduate medical students of a medical college in north Karnataka from May to October 2018. 178 students consisting of both boys and girls participated in the study and were interviewed using a pre-tested structured questionnaire. Data collected was analysed. Results: A total of 178 medical students participated in the study out of which 84 were males (48%) and 94 were females (52%). Majority of them (92%) resided in the hostel within the campus and only a few were local residents (8%). Mean age of subjects was 20±1.4 years. Taste was the main reason given by students which led to increased consumption of fast/junk food (46.7%). Chocolates were the most commonly consumed food followed by soft drinks. Majority of the students (87%) were well aware of the side effects of these fast/junk foods. Conclusions: Fast/junk foods preference and consumption are highly prevalent among medical students despite their knowledge about its health hazards.